Implementation of Field School Activities for Agricultural Technology Innovation in Klirong District, Kebumen Regency - Setiasih, Latifah Dwi; Wulan, Tyas Retno; Windiasih, Rili; Masrukin,; Sari, Lilik Kartika (Jurnal Indonesia Sosial Sains, 2025)
This research aims to analyze the implementation of Agricultural Technology Innovation Field School (SLPITP) activities in Klirong District, Kebumen Regency, focusing on post-harvest and harvest management training for farmers. The study addresses the need to improve farmers' knowledge and skills in implementing agricultural technology innovations to increase productivity and reduce post-harvest losses. The research employs a qualitative descriptive method using in-depth interviews, observations, and focus group discussions with 21 informants consisting of farmer group leaders, agricultural extension workers, village officials, and government staff from district and provincial agricultural offices. Data collection was conducted from November 2024 to March 2025 through purposive sampling technique. The results indicate that the SLPITP program successfully provided farmers with practical knowledge in six key areas: technology innovation socialization, power thresher operation, harvest loss calculation, special rice cultivation, vacuum packaging techniques, and follow-up action planning. The program involved 50 farmers from 10 farmer groups across three villages and provided essential equipment including power threshers, tarpaulins, moisture measuring tools, and vacuum packaging machines. Key challenges identified include limited initial farmer knowledge, low learning interest, capital constraints for post-harvest equipment, and the "ijon" purchasing system that discourages quality improvements. Despite these obstacles, the program achieved positive outcomes through hands-on learning approaches and provision of practical tools. The implications of this study suggest that field school programs effectively enhance farmer capabilities when supported by appropriate infrastructure and continuous follow-up activities. Future research should focus on long-term impact assessment and scaling strategies for broader implementation across different agricultural contexts.